Feminism in “Hustlers” Movie By Lorene Scafaria - Zazkia, Aulia Dela; Abdullah, Abdullah; Fitriyani, Fitriyani (State University of Makassar, 2024)
This study investigates the issues of feminism in Lorene Scafaria's